Draft Annual Plan 1973-74 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1973)
Prospects for increasing the area under multiple cropping in the State are encouraging with the availability of short duration varieties of crops and also for the reason that more area under irrigation projects are being brought under project areas. As a sequel, it is programmed to bring an additional area of 1.75 lakh hectares during 1973-74.
Planning and Cooperation Department
Planning and Cooperation Department Government of Andhra Pradesh